Depression and anxiety disorders amongst a cohort of infertile women attending an in-vitro fertilization clinic in south-western Nigeria. (2019)
Background: Psychological consequences of infertility have been documented in both developed and less developed countries. Depression and anxiety disorders have been identified as important causative factors. The prevalence of psychiatric morbidity amongst infertile women has been shown to be quite high with values as high as 46.4%. A high premium is placed on childbirth in Nigeria and failure to conceive is associated with disastrous consequences. Failed In-Vitro Fertilization (IVF) cycles have been implicated in psychological distress. Objective: This study aimed to determine the prevalence of anxiety and depression amongst infertile women undergoing IVF and to examine the psychosocial stressors associated with the development of these morbidities. Materials and Methods: A descriptive cross sectional study of fifty-one infertile women attending an In-Vitro Fertilization clinic in Lagos, South Western, Nigeria. Participants were recruited consecutively at their first consultation visit and a self-administered questionnaire consisting of sociodemographic information along with the Hospital Anxiety and Depression Scale (HADS) was completed by the participants. Data obtained from the respondents was analyzed using the Statistical Package for Social Sciences (IBM SPSS, New York) version 21. The Chi-Square statistic was used in testing for associations between categorical variables. Results: The mean age of the respondents was 38.96 ± 5.91 years with a range of 23-49 years. 76.5% (39/51) of the women had infertility greater than 5 years, while 49 % (25/51) of the women were aged 40 years and above with 96% (24/25) of this group experiencing infertility greater than 5 years. Anxiety was recorded in 24 respondents (47.1%) while Eighteen respondents (35.3%) had evidence of depression. Marital disharmony was found to be associated with the development of anxiety (P<0.05) Conclusion: The impact of infertility on the Nigerian couple can be devastating. Lack of support coupled with the overbearing and intrusive nature of family members predisposes to the development of psychosocial distress. We therefore recommend that Physicians pay attention to the psychosocial stressors experienced by infertile women prior to In Vitro Fertilization with the aim of ensuring appropriate referral for psychiatric assessment and treatment.